Analysis of Material Science and Techniques for Making Es Selendang Mayang - Destiani Rahmawati; Yudi Juniardi; Hidayatullah (Jurnal Penelitian Pendidikan IPA, 2025)
Es Selendang Mayang is a traditional drink from Betawi (Jakarta), Indonesia, popular for its sweet, savory flavor and colorful appearance (usually red, white, and green) resembling a scarf. The drink consists of three main components: a chewy cake called "selendang mayang," a savory coconut milk sauce, and a sweet brown sugar syrup, served with ice cubes for a refreshing treat. Globalization is changing the consumption patterns of traditional products that face the pressure of modern food. Es Selendang Mayang as a traditional Indonesian product has the potential to be developed. This research aims to analyze the chemical composition and physics of materials as well as ice-making techniques to produce quality products. The formulation of the problem includes the identification of materials and the influence of production techniques on the quality of the ice. Theoretical studies focus on materials science and traditional culinary production techniques. The methodology uses a qualitative approach with observational data collection, interviews, and laboratory tests. Data analysis was carried out in a systematic descriptive manner by comparing variations of materials and techniques. The results showed that the combination of rice flour and hunkwe produced the best texture and natural dyes supporting the aesthetics of the product. The implementation of research results can improve the quality and competitiveness of products and preserve local culinary culture.